BRCA1/2 and other predisposition genes in high-risk hormone receptor+/human epidermal growth factor receptor 2- breast cancer treated with endocrine therapy with or without palbociclib: a secondary PENELOPE-B study analysis : original reports : biomarkers - Hahnen, Eric Thomas; Hauke, Jan; Gelmon, Karen; Marmé, Frederik; Ernst, Corinna; Martin, Miguel; Untch, Michael; Bonnefoi, Hervé; Knudsen, Erik; Im, Seock-Ah; DeMichele, Angela; Van't Veer, Laura; et al. (JCO precision oncology, 2025)
Purpose - The PENELOPE-B trial (ClinicalTrials.gov identifier: NCT01864746) recruited patients with hormone receptor+/human epidermal growth factor receptor 2- early breast cancer without a pathological complete response after taxane-containing neoadjuvant chemotherapy and at a high risk of relapse. Patients were randomly assigned (1:1) to receive 13 cycles of palbociclib once daily or placebo on days 1-21 in a 28-day cycle in addition to endocrine therapy (ET). PENELOPE-B did not show improved invasive disease-free survival (iDFS) after adding palbociclib to ET. This retrospective analysis investigated the impact of germline pathogenic variant (PV) status of BRCA1/2 and non-BRCA1/2 cancer predisposition genes on the outcomes of PENELOPE-B trial patients. - Methods - In total, 445 patients were sampled following a case-cohort design and 442 were analyzed for germline PVs. Statistical analyses were performed for time-to-event end points (iDFS, distant disease-free survival [DDFS], and overall survival [OS]). - Results - Of the 442 patients, 42 carried PVs in any cancer predisposition gene; 15 carried BRCA1/2 PVs. Irrespective of the treatment arms, PV status was not a prognostic factor. Regarding the treatment arms in BRCA1/2 PV carriers, numerically better 3-year outcomes were observed in the palbociclib arm (iDFS, 95%; DDFS, 95%; OS, 100%) than in the placebo arm (iDFS, 72.8%; DDFS, 72.8%; OS, 87.5%; hazard ratios palbociclib v placebo 0.349 [iDFS] and 0.562 [DDFS], not calculated for OS, too few events). In patients without BRCA1/2 PVs, the differences in 3-year outcomes were negligible. PVs in non-BRCA1/2 cancer predisposition genes did not influence the efficacy of palbociclib, although gene-specific effects could not be excluded. - Conclusion - Patients with BRCA1/2 PVs had numerically better outcomes after palbociclib. However, the number of BRCA1/2 carriers was small. Larger randomized clinical trials should consider the PV status to further evaluate whether BRCA1/2 PV carriers benefit from cyclin-dependent kinase 4 and 6 inhibitor treatment.